2012
DOI: 10.1038/oby.2011.167
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Mitochondrial Energetics During Catch‐Up Fat With High‐Fat Diets Rich in Lard or Safflower Oil

Abstract: We have investigated whether altered hepatic mitochondrial energetics could explain the differential effects of high‐fat diets with low or high ω6 polyunsaturated fatty acid content (lard vs. safflower oil) on the efficiency of body fat recovery (catch‐up fat) during refeeding after caloric restriction. After 2 weeks of caloric restriction, rats were isocalorically refed with a low‐fat diet (LF) or high‐fat diets made from either lard or safflower oil for 1 week, and energy balance and body composition changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
3
16
0
1
Order By: Relevance
“…A previous supplementation trial in postmenopausal women reported that a daily dose of 8 g PUFA (safflower oil) increased lean tissue and reduced trunk fat (48). In accordance, rats isocalorically fed with PUFAs (high in linoleic acid) gained more lean tissue and less fat compared with an SFA-rich diet, in line with similar studies (16,17,49,50). The mechanism behind these observations remains to be determined.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…A previous supplementation trial in postmenopausal women reported that a daily dose of 8 g PUFA (safflower oil) increased lean tissue and reduced trunk fat (48). In accordance, rats isocalorically fed with PUFAs (high in linoleic acid) gained more lean tissue and less fat compared with an SFA-rich diet, in line with similar studies (16,17,49,50). The mechanism behind these observations remains to be determined.…”
Section: Discussionsupporting
confidence: 76%
“…Concentrations of D-3-hydroxybutyrate were, however, if anything, lower with PUFAs than SFAs, thus not supporting a differential effect on hepatic fat oxidation. Animal studies have also indicated that SFAs, compared with PUFAs, lower brown tissue adipose activity and thermogenesis (16)(17)(18)(19)(39)(40)(41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies show that the composition of dietary fat could play a major role in liver fat accumulation with polyunsaturated fatty acids PUFAs adversely 25 and saturated fatty acids SFAs directly related with liver fat and liver fat biomarkers 26 . Animals fed high fat diets incorporated with PUFAs reduced liver fat accumulation compared to SFA diets 27 . In this respect, Bjermo et al 21 indicate that an isocaloric diet rich in PUFAs submitted for ten weeks reduced the content of liver fat and tended to reduce insulin resistance compared to a diet rich in SFAs in individuals with abdominal obesity and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies (Crescenzo et al, 2003; De Andrade et al, 2015), we observed that after a period of caloric restriction, when rats are refed with a low fat diet, they exhibit a reduction in energy expenditure and an increase in metabolic efficiency that give rise to an elevated rate of body fat deposition (even in absence of hyperphagia), together with a reduced insulin sensitivity (Crescenzo et al, 2003; Cettour-Rose et al, 2005). The above metabolic alterations are exacerbated by refeeding on a high fat diet (Dulloo and Girardier, 1992; Crescenzo et al, 2003, 2012; Marcelino et al, 2013). Indeed, it was shown that glucose homeostasis is impaired during refeeding with high fat diets rich in lard, mainly containing saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA), partly because the pathway of de novo lipogenesis is markedly inhibited in liver and white adipose tissue (WAT) (Marcelino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%